Perspective Plan for Telangana Volume I Resource Inventory Andhra Pradesh - Planning Commission (Planning Commission, 1956)
The Telangana region of Andhra Pradesh State comprises of the nine districts of Mahbubnagar, Hyderabad, Medak, Nizamabad, Adilabad, Karimnagar, Warangal, Khammam and Nalgonda. Till 1st November, 1956, these nine districts formed part of the erstwhile State of Hyderabad. Under the scheme of Reorganisation of States on 1st November 1956, the nine districts of Telangana region were added to the erstwhile Andhra State to form the present State of Andhra Pradesh.
Planning and Co-operation Department, Andhra Pradesh